1979
DOI: 10.1161/01.cir.59.5.938
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation of exercise capacity in patients with Prinzmetal's variant angina: role of exercise-induced coronary arterial spasm.

Abstract: SUMMARY Thirteen patients with Prinzmetal's variant angina performed treadmill exercise tests in the early morning and in the afternoon of the same day. The attacks with ST elevation were induced repeatedly in all 13 patients in the early morning, but in only two patients in the afternoon.Propranolol did not suppress the exercise-induced attacks in all 13 patients. Diltiazem suppressed the attacks in all 13 patients and phentolamine in eight of the nine patients.Coronary arteriograms demonstrated that spasm oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
3
7

Year Published

1981
1981
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(135 citation statements)
references
References 4 publications
4
121
3
7
Order By: Relevance
“…Our findings are in agreement with clinical reports of exacerbation of coronary vasospasm by /3-adrenergic blockade in some patients with variant anginal9 20 and other investigators who have demonstrated coronary vasospasm after propranolol during sympathetic stimulation with exercise or with subcutaneous injection of epinephrine, a mixed a-and 13-adrenergic agonist. 5 precise effect of ,3-adrenergic blockade on coronary vascular tone in man is difficult to define. A reduction of coronary blood flow after propranolol associated with a widening of the arterial-coronary sinus oxygen difference has suggested a vasoconstrictor effect,34 3 while narrowing of transcoronary oxygen difference after,8 blockade is consistent with reduction of myocardial metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with clinical reports of exacerbation of coronary vasospasm by /3-adrenergic blockade in some patients with variant anginal9 20 and other investigators who have demonstrated coronary vasospasm after propranolol during sympathetic stimulation with exercise or with subcutaneous injection of epinephrine, a mixed a-and 13-adrenergic agonist. 5 precise effect of ,3-adrenergic blockade on coronary vascular tone in man is difficult to define. A reduction of coronary blood flow after propranolol associated with a widening of the arterial-coronary sinus oxygen difference has suggested a vasoconstrictor effect,34 3 while narrowing of transcoronary oxygen difference after,8 blockade is consistent with reduction of myocardial metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the attack can be induced by mild exercise in the morning. On the other hand, an attack cannot be induced during the afternoon of the same day (45,46). Thus, one of the most important clinical features of coronary spasm is its circadian variation.…”
Section: Circadian Variation Of Coronary Spasmmentioning
confidence: 99%
“…Although our study population did not comprise a very large number of patients, the use of long-term electrocardiography over 48 hours certainly diminished the importance of evaluating only 39 patients. Regarding the findings of the long-term electrocardiography as a function of the distribution of ischemic events throughout the 24 hours of a day, we should first point out that the option of dividing the day into 4-hour intervals and for defining them from 11:00 pm to 3:00 am, from 3:00 am to 7:00 am and so on, was based on the previous experience of other authors 8,9,12,13,[15][16][17] , who reported, as a rule, a higher frequency of ischemic events from dawn until the first hours in the morning, the so-called circadian variation of ischemia, with or without symptoms. This evidence was based on studies that evaluated the incidence of acute myocardial infarction throughout the 24 hours of a day 18,19 , which showed a higher incidence between 3:00 am and 8:00 am.…”
Section: Discussionmentioning
confidence: 99%